The vasculature of nurse cells infected with non-encapsulated Trichinella species. - Pathamet Khositharattanakool (2018)
The vasculature surrounding the nurse cells of encapsulated Trichinella spiralis has been described previously. It has been postulated the function of these vessels is to support the growth of the parasite. We describe here for the first time the vasculature surrounding the nurse cells of non-encapsulated T. pseudospiralis and T. papuae. Similar to the vasculature of uninfected muscle cells, the vessels surrounding non-encapsulated Trichinella nurse cells are dense and branched longitudinally along the long axis of the muscle cells; they also appear to be similar in diameter. The netting pattern of enlarged vessels found around T. spiralis (encapsulated) nurse cells is not present in non-encapsulated Trichinella infections. The vessels surrounding non-encapsulated Trichinella nurse cells seem to exist prior to parasite invasion of the muscle cell.